Burying autumn poetry, friendship and loss - Hu, Ying 1962- (Harvard East Asian monographs, 2016)
"A linked biographical study of the enduring friendship of three women writers...Qiu Jin, Wu Zhiying. and Xu Zihua...in late Qing and early Republican China"...